2020
DOI: 10.3389/fchem.2020.617463
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent AIE-Active Materials for Two-Photon Bioimaging Applications

Abstract: Fluorescence imaging has been widely used as a powerful tool for in situ and real-time visualization of important analytes and biological events in live samples with remarkably high selectivity, sensitivity, and spatial resolution. Compared with one-photon fluorescence imaging, two-photon fluorescence imaging exhibits predominant advantages of minimal photodamage to samples, deep tissue penetration, and outstanding resolution. Recently, the aggregation-induced emission (AIE) materials have become a preferred c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 117 publications
0
22
0
Order By: Relevance
“…Indeed, the discovery of this behaviour stimulated intense interest in the search for other AIE molecules, and recent years have seen an ever‐increasing library of AIE luminogenic (AIEgens) materials developed. [5] In this context, tetraphenylethene (TPE) derivatives have risen to prominence as synthetically accessible, modular, multivalent scaffolds for AIEgens in the construction of bio‐imaging probes,[ 6 , 7 ] optoelectronic devices [8] and responsive materials. [ 9 , 10 , 11 , 12 ] In addition to their role as highly sensitive luminescent reporter groups, TPE derivatives are also of interest by virtue of their potential to serve as photoswitchable platforms with large degrees of spatial control.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the discovery of this behaviour stimulated intense interest in the search for other AIE molecules, and recent years have seen an ever‐increasing library of AIE luminogenic (AIEgens) materials developed. [5] In this context, tetraphenylethene (TPE) derivatives have risen to prominence as synthetically accessible, modular, multivalent scaffolds for AIEgens in the construction of bio‐imaging probes,[ 6 , 7 ] optoelectronic devices [8] and responsive materials. [ 9 , 10 , 11 , 12 ] In addition to their role as highly sensitive luminescent reporter groups, TPE derivatives are also of interest by virtue of their potential to serve as photoswitchable platforms with large degrees of spatial control.…”
Section: Introductionmentioning
confidence: 99%
“…As curcumin is a fluorescent molecule, metal-curcumin complexes may be used in biological imaging and radioimaging. It has been reported that materials with large two-photon absorption cross sections are better for the bioimaging of living cells and tissues [93]. As curcumin complexes with copper have properties of higher quantum yield and larger two-photon absorption, they have been investigated for biological imaging and radioimaging.…”
Section: Application Of Metal-curcumin Complex On Biological Imaging and Radioimagingmentioning
confidence: 99%
“…[ 38 ] In addition, π–π stacking of AIE molecules can be effectively avoided owing to their nonplanar conformations. [ 37 ] Due to their unique optical properties, AIE probes possess exceptional advantages in anti‐photobleaching [ 39,40 ] and maintaining photophysical properties [ 41 ] in physiological environments. Additionally, ascribed to diverse surface capping agents, such as proteins, [ 42 ] lipids, [ 43 ] and poly(ethylene glycol) (PEG) derivatives, [ 44 ] AIE probes have exhibited reduced cytotoxicity and remarkable biocompatibility.…”
Section: Introductionmentioning
confidence: 99%